Experimental Study on Cryogenic Compressed Hydrogen Jet Flames - Shishuai Nie; Peng Cai; Huan Liu; Yonghao Zhou; Yi Liu; Anfeng Yu (Fire)
Cryogenic compressed hydrogen (CcH2) technology combines the advantages of high pressure and low temperature to achieve high hydrogen storage density without liquefying the hydrogen, which has broad application prospects. However, the safety concerns related to cryogenic hydrogen need to be carefully addressed beforehand. In the present work, cryogenic hydrogen jet flames are experimentally investigated for various release pressures and initial temperatures. The flame length and thermal radiation flux were measured for horizontally releasing with nozzle diameters of 0.5–2 mm, temperatures ranging from 93 to 298 K, and initial pressures of 2–10 MPa. The results show that the flame length is dependent on the nozzle diameter, stagnation pressure and temperature. At a given pressure, the flame length, size and total radiant power increase with decreasing temperature, which is attributed to the lower jet flow velocity and higher density of low-temperature hydrogen. The normalized flame length Lf/D is correlated with the pressure ratio and temperature ratio. The correlation can be used to predict the flame length at various hydrogen pressures and temperatures. The normalized flame length of the cryogenic hydrogen jet flame is greater than that of the room-temperature hydrogen jet flame. The radiative heat flux of the flame can be predicted by the mass flow rate of the jet flow.